Analisis pemanfaatan limbah beton ready mix dari PT X berlokasi di Surabaya sebagai substitusi agregat kasar terhadap kuat tekan beton - Rizqi Dwi Nanda Abdur Rohman; Nurul Rochmah; Bantot Sutriono (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Concrete is the most commonly used primary construction material, so increasing demand for raw materials can encourage continuous mining of coarse aggregates, which risks causing natural resource scarcity and environmental damage such as landslides. Thus, alternative materials are needed that are still rarely used but according to applicable standards. Based on this, the author took the initiative to utilize concrete waste as a substitute for coarse aggregate in making new concrete. The concrete waste used comes from ready mix test objects of PT X located in Surabaya, which produces around 8m³ of test object waste that is disposed of every month. The contribution in this study is to reduce concrete waste that pollutes the environment and evaluate whether concrete waste with similar quality can exceed the compressive strength of normal concrete. Therefore, this study aims to analyze the utilization of ready-mix concrete waste stone from PT X located in Surabaya as a substitute material for coarse aggregate in concrete mixtures with a focus on its effect on compressive strength. This study uses a quantitative method through laboratory testing with cylindrical concrete samples with a diameter of 15 cm and a height of 30 cm, totaling 36 samples. These samples will be used for concrete compressive strength tests at the ages of 7, 14, and 28 days. There are two substitution variations, namely 0% and 100%, and two planned qualities, namely Fc 25 MPa for a mixture with K-300 quality concrete waste substitution, and Fc 30 MPa for a mixture with K-400 quality concrete waste substitution. The optimum compressive strength value for the design quality f'c 25 was obtained at 21.26 MPa with 0% coarse aggregate substitution, which is 4.78% higher than 100% coarse aggregate substitution. Meanwhile, for the design quality f'c 30, the optimum value was recorded at 24.59 MPa with 0% coarse aggregate substitution, which is 10.9% higher than 100% coarse aggregate substitution. These results indicate that the compressive strength obtained has not been able to achieve the planned compressive strength target and also the use of concrete waste stone as a substitute for coarse aggregate is highly discouraged.